Emergence of sub-optimal land utilization patterns in Indian cities. Issue 6 (1st November 2020) - Byahut, Sweta; Patel, Bimal; Mehta, Jignesh
ABSTRACT: This paper examines the urban morphology of Ahmedabad, a large and rapidly growing Indian city, to determine land utilization efficiency. It provides a nuanced understanding of land consumption patterns in public and private domains, and how sub-optimal land development patterns emerge. Urban form parameters analysed include public streets, building footprints, and public and private open spaces. The results show that land utilization is sub-optimal, with less land available under public domain and more land consumed as private open spaces (especially as margins and setbacks) leading to excessive fragmentation. Indian cities should rationalize their development regulations to improve land utilization outcomes.